2001
DOI: 10.1016/s0022-5347(05)65617-0
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Structured Withdrawal Program to Prevent Relapse of Nocturnal Enuresis

Abstract: The structured withdrawal program significantly reduces relapse rates, and offers an alternative and rapid means of successfully withdrawing medication. It is argued that the influential variable concerns the ability of the child to shift attribution for success from an external source (that is medication) to an internal focus (that is changes in themselves).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 19 publications
0
12
0
3
Order By: Relevance
“…If the child does not achieve complete dryness, or if wetting resumes once treatment is withdrawn, it should be continued/resumed. There is some evidence that structured withdrawal of medication may reduce relapse rates following its discontinuation [4, 29]. If a second voiding diary indicates nocturnal urinary production is not reduced, consider a dose increase (if maximum recommended dose has not been reached); otherwise, refer the child to a specialist.…”
Section: Desmopressin Therapymentioning
confidence: 99%
“…If the child does not achieve complete dryness, or if wetting resumes once treatment is withdrawn, it should be continued/resumed. There is some evidence that structured withdrawal of medication may reduce relapse rates following its discontinuation [4, 29]. If a second voiding diary indicates nocturnal urinary production is not reduced, consider a dose increase (if maximum recommended dose has not been reached); otherwise, refer the child to a specialist.…”
Section: Desmopressin Therapymentioning
confidence: 99%
“…Thus, removing the alarm or medication removes what the child believes to be the reason for success, and relapse consequently follows. Recently, Butler et al [91] reported an 8-week withdrawal programme speci®cally designed for preventing relapse on removal of medication. The programme focuses on engaging the child in a process of internalizing success and highlighting the effective process by which this is accomplished, whether it be increased arousability or improved AVP release.…”
Section: Preventing Relapsementioning
confidence: 99%
“…Consiste en administrar la dosis completa de fármaco, disminuyendo quincenalmente los días de tratamiento hasta suspenderlo. Es una terapia conductual que añade un efecto curativo a la finalización del tratamiento con desmopresina 12 .…”
Section: ¿Cómo Mejorar Los Resultados Con Desmopresina?unclassified